Attack of the Bum-Biting Sharks - Kain, Matt; Illustrated by Field, Jim (London Macmillan Children's Books, 2009)
When friends Jez and Charlie meet potion maker Quentin Quirk and discover his amazing magic works, chaos, action and laughter are only a freaky spell away!
Include illustrations
Keywords: Magic -- Male friendship -- Brothers and sisters